Amyotrophic Lateral Sclerosis: An Analysis of the Electromyographic Fatigue of the Masticatory Muscles - Ligia Maria Napolitano Gonçalves; Selma Siéssere; Flávia Argentato Cecilio; Jaime Eduardo Cecilio Hallak; Paulo Batista de Vasconcelos; Wilson Marques Júnior; Isabela Hallak Regalo; Marcelo Palinkas; Simone Cecilio Hallak Regalo (Prague Medical Report, 2022)
Amyotrophic lateral sclerosis is a chronic degenerative disease that affects motor neurons, thereby promoting functional changes in the human body. The study evaluated the electromyographic fatigue threshold of the masseter and temporal muscles of subjects with amyotrophic lateral sclerosis. A total of eighteen subjects were divided into two groups: amyotrophic lateral sclerosis (n=9) and disease-free control (n=9). The groups were equally divided according to gender (7 males, 2 females). The fatigue threshold was analysed using median frequencies obtained during the 5-second window (initial [IP], mid [MP], and final [FP] periods) of electromyographic signalling of the masseter and temporal muscles bilaterally, with reduction in muscle force during maximal voluntary dental clenching. Significant difference (p<0.05) in the left temporal muscle: IP (p=0.05) and MP (p=0.05) periods was demonstrated. The amyotrophic lateral sclerosis group showed a decrease in median frequency of the electromyographic signal of the masseter and temporal muscles compared to the control group. Amyotrophic lateral sclerosis promotes functional impairment of the stomatognathic system, especially at the electromyographic fatigue threshold of the masticatory muscles.